Flood-related disaster communication and humanitarian logistics - Puteri Fadzline, Muhamad Tamyez; Gerth, Natalie Christiane Isabella; Khairul Firdaus, Anuar (KnE Social Sciences, 2019)
During the annual monsoon season, Malaysia is often affected severely by floods as a result of heavy rainfall and poor irrigation. Every year, thousands of people have to be relocated and be evacuated from their homes. Thus, this research is aimed to look at two central aspects of disaster management in the context of flood disaster management in Kuantan, Pahang. Using a mixed-method approach, first, the effectiveness of communication mechanisms in the case of floods is investigated with quantitative analysis using descriptive design. Secondly, this research takes a closer look at the underlying logistical framework found in flood disaster contexts and identifies its critical success factors. For this, a qualitative research approach is taken. Using thematic analysis, in-depth semi-structured interviews are analyzed to arrive at conclusions regarding the critical success factors. Investigating in the effectiveness of disaster communication, it has become apparent that communication between authorities, agencies, non-government organizations or NGOs and flood victims are still in need of improvement, as the suggestions made by participants of the study suggests, both in regard to emergency updates as well as to heightening community awareness on the right actions to take in preparation of upcoming floods. The critical success factors for humanitarian response in the case of flood management include coordination, communication, knowledge, and preparedness. In it crucial to safeguard communities, thus, the unambiguous and clear standard of procedures or SOPs need to be in place at the integrated agencies for them to be understood and known by the individuals who execute them.